L‐ornithine L‐aspartate for prevention and treatment of hepatic encephalopathy in people with cirrhosis - Goh, Ee Teng (Cochrane Database Syst Rev, 2018)
BACKGROUND: Hepatic encephalopathy is a common complication of cirrhosis and has high associated morbidity and mortality. The condition is classified as overt if it is clinically apparent or minimal if only evident though psychometric testing. The exact pathogenesis of this syndrome is unknown although ammonia is thought to play a key role. L‐ornithine L‐aspartate has ammonia‐lowering properties and may, therefore, benefit people with cirrhosis and hepatic encephalopathy. OBJECTIVES: To evaluate the beneficial and harmful effects of L‐ornithine L‐aspartate versus placebo, no intervention, or other active interventions in people with cirrhosis and hepatic encephalopathy. SEARCH METHODS: We undertook electronic searches of The Cochrane Hepato‐Biliary Group Controlled Trials Register, CENTRAL, MEDLINE, Embase, LILACS and Science Citation Index Expanded to December 2017 and manual searches of meetings and conference proceedings; checks of bibliographies; and corresponded with investigators and pharmaceutical companies. SELECTION CRITERIA: We included randomised clinical trials, irrespective of publication status, language, or blinding. We included participants with cirrhosis who had minimal or overt hepatic encephalopathy or who were at risk for developing hepatic encephalopathy. We compared: L‐ornithine L‐aspartate versus placebo or no intervention; and L‐ornithine L‐aspartate versus other active agents such as non‐absorbable disaccharides, antibiotics, probiotics, or branched‐chain amino acids. DATA COLLECTION AND ANALYSIS: Two review authors, working independently, retrieved data from published reports and correspondence with investigators and pharmaceutical companies. The primary outcomes were mortality, hepatic encephalopathy, and serious adverse events. We undertook meta‐analyses and presented the results as risk ratios (RR) and mean differences (MD) with 95% confidence intervals (CI). We assessed bias control using the Cochrane Hepato‐Biliary Group domains; we evaluated the risk of publication bias and other small trial effects in regression analyses; conducted subgroup and sensitivity analyses; and performed Trial Sequential Analyses. We determined the quality of the evidence using GRADE. MAIN RESULTS: We identified 36 randomised clinical trials, involving at least 2377 registered participants, which fulfilled our inclusion criteria including 10 unpublished randomised clinical trials. However, we were only able to access outcome data from 29 trials involving 1891 participants. Five of the included trials assessed prevention, while 31 trials assessed treatment. Five trials were at low risk of bias in the overall assessment of mortality; one trial was at low risk of bias in the assessment of the remaining outcomes. L‐ornithine L‐aspartate had a beneficial effect on mortality compared with placebo or no intervention when including all trials (RR 0.42, 95% CI 0.24 to 0.72; I(2) = 0%; 19 trials; 1489 participants; very low quality evidence), but not when the analysis was restricted to the trials at low risk of bias (RR 0.47, 95% CI 0.06 to 3.58; 4 trials; 244 participants). It had a beneficial effect on hepatic encephalopathy compared with placebo or no intervention when including all trials (RR 0.70, 95% CI 0.59 to 0.83; 22 trials; 1375 participants; I(2) = 62%; very low quality evidence), but not in the one trial at low risk of bias (RR 0.96, 95% CI 0.85 to 1.07; 63 participants). The analysis of serious adverse events showed a potential benefit of L‐ornithine L‐aspartate when including all randomised clinical trials (RR 0.63, 95% CI 0.45 to 0.90; 1 trial; 1489 participants; I(2) = 0%; very low quality evidence), but not in the one trial at low risk of bias for this outcome (RR 0.83, 95% CI 0.15 to 4.65; 63 participants). The Trial Sequential Analyses of mortality, hepatic encephalopathy, and serious adverse events found insufficient evidence to support or refute beneficial effects. Subgroup analyses showed no difference in outcomes in the trials evaluating evaluating the prevention or treatment of either overt or minimal hepatic encephalopathy or trials evaluating oral versus intravenous administration We were unable to undertake a meta‐analysis of the three trials involving 288 participants evaluating health‐related quality of life. Overall, we found no difference between L‐ornithine L‐aspartate and placebo or no intervention in non‐serious adverse events (RR 1.15, 95% CI 0.75 to 1.77; 14 trials; 1076 participants; I(2) = 40%). In comparison with lactulose, L‐ornithine L‐aspartate had no effect on mortality (RR 0.68, 95% CI 0.11 to 4.17; 4 trials; 175 participants; I(2) = 0%); hepatic encephalopathy (RR 1.13, 95% CI 0.81 to 1.57); serious adverse events (RR 0.69, 95% CI 0.22 to 2.11); or non‐serious adverse events (RR 0.05, 95% CI 0.01 to 0.18). In comparison with probiotics, L‐ornithine L‐aspartate had no effect on mortality (RR 1.01, 95% CI 0.11 to 9.51); serious adverse events (RR 1.07, 95% CI 0.23 to 4.88); or changes in blood ammonia concentrations from baseline (RR ‐2.30 95% CI ‐6.08 to 1.48), but it had a possible beneficial effect on hepatic encephalopathy (RR 0.71, 95% CI 0.56 to 0.90). Finally, in comparison with rifaximin, L‐ornithine L‐aspartate had no effect on mortality (RR 0.33, 95% CI 0.04 to 3.03; 2 trials; 105 participants); hepatic encephalopathy (RR 1.06, 95% CI 0.57 to 1.96); serious adverse events (RR 0.32, 95% CI 0.01 to 7.42), or non‐serious adverse events (RR 0.32, 95% CI 0.01 to 7.42). AUTHORS' CONCLUSIONS: The results of this review suggest a possible beneficial effect of L‐ornithine L‐aspartate on mortality, hepatic encephalopathy, and serious adverse events in comparisons with placebo or no‐intervention, but, because the quality of the evidence is very low, we are very uncertain about these findings. There was very low quality evidence of a possible beneficial effect of L‐ornithine L‐aspartate on hepatic encephalopathy, when compared with probiotics, but no other benefits were demonstrated in comparison with other active agents. Additional access to data from completed, but unpublished trials, and new randomised placebo‐controlled, double‐blind clinical trials are needed.